In-situ sensor response of copper oxide urchin-like structures - Orlandi, M. O. [UNESP]; Felix, A. A. [UNESP]; Suman, P. H. [UNESP]; Varela, J. A. [UNESP]; Volanti, D. P. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
In this work we report an advanced study of gas sensor performance of copper oxide (CuO) urchin-like structures synthesized by microwave assisted hydrothermal method. Copper oxide in an interesting p-type semiconductor in order to study the mechanisms related to the sensor response of CuO structures, we developed a special sample holder which enables the simultaneous characterization of materials by X-ray absorption near edge structure (XANES) and electrical measurements. Quantitative XANES analyses showed that the CuO material can have its surface completely reduced when exposed to H2 in N2 baseline and electrical measurements confirm the abrupt decrease in the material resistance. This superficial reduction is reversible after exposition of sample to a synthetic air atmosphere. Sensor response models for CuO material based on these findings were proposed.
Keywords: copper oxide; nanomaterials; Sensors